Ceremonial language and social cohesion: An analysis of Seumapa in Acehnese wedding traditions - Kismullah Abdul Muthalib; Dohra Fitrisia; Nia Zahara (Studies in English Language and Education, 2024)
The Seumapa ceremony, a rhyming exchange ritual performed by a Syekh (reciter) representing both the brides (darabar) and the bridegrooms (lintbar) parties during Acehnese wedding ceremonies before the groom is allowed into the house of Acehnese society in Indonesia, stands as a testament to the role of cultural rituals in capturing and spreading societal values and norms. This study attempts to analyze this ceremony to reveal the social community, practice, and symbolic language within the Acehnese wedding context. It is to further understand how they shape the social cohesion and identity of the Acehnese community. By employing observations on three wedding ceremonies, and interviews with three elders of the community, the analysis of Seumapas cultural values reveals the ceremonys emphasis on etiquette, respect, social and religious identity, customary knowledge, and educational significance. Ritualistic greetings and gift exchanges portray communal harmony, while symbolic acts symbolic acts like lifting the curtain and presenting hantaran (ceremonial gifts) from the groom to the bride and vice versa represent social identity and mutual responsibility. The integration of religious knowledge depicts the communitys prioritization of spiritual preparedness, and the use of symbolic and metaphorical language reflects societal values and aspirations, signifying the importance of wisdom, respect, and communal bonds in preserving Acehnese cultural identity.